2009
DOI: 10.1007/s00467-009-1208-8
|View full text |Cite
|
Sign up to set email alerts
|

Retarded hand growth due to a hemodialysis fistula in a young girl

Abstract: Long-term presence of an arteriovenous hemodialysis fistula (AVF) may lead to alterations in hand perfusion. In the case reported here, a 14-year-old girl developed pain associated with hand ischemia 5 years after a successful kidney transplantation. At age 8 years, she required a period of hemodialysis using an autogenous left upper arm AVF. Compared to the healthy right hand, a smaller ischemic left hand was observed in the presence of a patent AVF. Access flow was 1400 ml/min. Seldinger angiography demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A study of 434 accesses in children found hemodialysis access-induced distal ischemia in 9%, but high access flow in only 1% (9). Frank van Hoek et al (13) reported a girl with a small ischemic left hand in the ipsilateralto-AVF hand with a patent AVF, whereas the contralateral-to-AVF hand was normal. They surmised that the abnormal AVF forearm was due to chronic tissue hypoxia and speculated that the AVF resulted in decreased nutrients being supplied to the distal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 434 accesses in children found hemodialysis access-induced distal ischemia in 9%, but high access flow in only 1% (9). Frank van Hoek et al (13) reported a girl with a small ischemic left hand in the ipsilateralto-AVF hand with a patent AVF, whereas the contralateral-to-AVF hand was normal. They surmised that the abnormal AVF forearm was due to chronic tissue hypoxia and speculated that the AVF resulted in decreased nutrients being supplied to the distal tissues.…”
Section: Discussionmentioning
confidence: 99%